2007
DOI: 10.1186/1476-7120-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Distal left circumflex coronary artery flow reserve recorded by transthoracic Doppler echocardiography: a comparison with Doppler-wire

Abstract: BackgroundCoronary flow reserve (CFR) recording by means of transthoracic echocardiography (TTDE) in all the main distal coronary arteries is a challenge for advanced echocardiography. Validation studies of TTDE versus Doppler-wire (DW) recordings are available for Left Anterior Descending artery (LAD) and the Posterior Descending coronary artery (PD), but lacking for the more technically challenging Left Circumflex coronary artery (LCx).AimTo evaluate the reliability of TTDE in assessing CFR in LCx when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For the first time, Hozumi et al [1] diagnosed left anterior descending coronary artery (LAD) stenosis by this method, and this method has been applied to the circumflex [6], right [7] and three major coronary arteries [8]. Moreover, this method has been extended to evaluate coronary microvascular function in patients without significant stenosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…For the first time, Hozumi et al [1] diagnosed left anterior descending coronary artery (LAD) stenosis by this method, and this method has been applied to the circumflex [6], right [7] and three major coronary arteries [8]. Moreover, this method has been extended to evaluate coronary microvascular function in patients without significant stenosis [9][10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…[24][25][26] The fewer studies performed in other arteries have shown that a reliable test could be obtained in 70-81% and 43-72% in the right and the circumflex coronary artery, respectively. [27][28][29] In a small study on 10 healthy volunteers, CFR assessed by TTDE was compared with that obtained by PET, showing again a high agreement with the reference method. 30 Accordingly, validation studies have shown good reliability in identifying patients with reduced CFR.…”
Section: Validation Studies and Normal Valuesmentioning
confidence: 87%
“…21 Interestingly, the few studies that assessed intraindividual variability of TTDE results have shown high reproducibility of measures, with a coefficient of variation not exceeding 6%. 22,23 Several studies have investigated the reliability of TTDE in assessing CMV dilator function by comparing the results with those obtained with the gold standard method of intracoronary Doppler flow wire (ICDW) recording [24][25][26][27][28][29] (Table 3). These validation studies, usually performed in patients undergoing coronary angiography for suspected CAD, have shown that TTDE is feasible in the majority of patients and show a high agreement with CFR obtained with ICDW recording, with correlation coefficients ranging from 85 to 97% and consistent concordance by Bland-Altman analysis.…”
Section: Validation Studies and Normal Valuesmentioning
confidence: 99%
“…Doppler flow wires can be used during interventional cases for CFR measurement (2,25). Since the measurement relies on a specific angle between the ultrasound beam and the vessel direction, the accuracy is difficult to control and requires significant manipulation, especially in diseased, tortuous vessels (18).…”
Section: Discussionmentioning
confidence: 99%